POSSIBILITY OF BONE METABOLISM MODULATOR (STRONTIUM RANELATE) USAGE FOR THE TREATMENT OF WOMEN WITH POSTMENOPAUSAL OSTEOPOROSIS AND ARTERIAL HYPERTENSION - N. J. Hozjainova; V. M. Tsareva; T. V. Brook; M. S. Bezaltynnyh (Столичная издательская компания, 2016)
Aim. To study effect of the bone metabolism modulator strontium ranelate on bone mineral density (BMD) and to evaluate it pleiotropic effects on cardiovascular remodeling in women with postmenopausal osteoporosis (PO) and a arterial hypertension (HT). Material and methods. 45 women with PO, HT (1-2 stage) and medium/high cardiovascular risk were included in the study. 23 patients of the main group received strontium ranelate 2 g once daily additionally to antihypertensive and calcium replacement therapies. Before therapy and after 10 months MBD was evaluated by dual-energy x-ray absorbtiometry (DEXA) with usage of peripheral densitometer. Strontium ranelate effects on carotid intima-media thickness (duplex scanning) and morphofunctional cardiac indices (echocardiography) also were assessed. Results. Strontium ranelate therapy in patients with PO and HT leads to BMD rising and retardation of cardiovascular remodeling. Conclusion. Strontium ranelate is effective antiosteoporotic drug with positive influence on morphofunctional cardiac indices and carotid intima-media thickness.